TextCrunch: an interactive text mining application / Noorezatty Mohd Yusop … [et al.] - Mohd Yusop, Noorezatty; Khairol Azmi, Nurul Nisa’; Abdul Wahab, Nurul Aini; Mohd Rosli, Intan Nur Izzaty (Faculty of Computer and Mathematical Sciences, 2023)
TextCrunch, a web application, enhances teaching and learning in text mining analysis. It benefits educators, researchers, and learners. Operating on the Shiny framework, it simplifies text data analysis with its user-friendly interface. Key features include real-time results from uploaded text data and various visualizations. This empowers users to draw accurate conclusions. Whether you're a novice or an expert, TextCrunch accommodates all levels of expertise. In summary, TextCrunch is a valuable tool for educators, researchers, and learners involved in text mining, promising to revolutionize the field and advance knowledge.